Epistemologi Perkembangan Tafsir Era Sahabat - Aziz, Hayatullah Hilmi (Al-Jadwa: Jurnal Studi Islam, 2023)
The development of interpretations needs to be observed as a scientific treasure, including the development of the interpretations of the Companions period which became the embryos of the development of the interpretations of the Koran after the time of the Prophet. Therefore, it is important to know how the development of interpretation at the time of the Companions. This paper uses a descriptive analysis method with a qualitative approach and applies library research types. The result is that the exegesis of the Companions period does not yet have special works like those of the later era, so the exegesis is still scattered randomly like hadith. Interpretations of friends also experience differences, but tend to be more diverse. There are three sources used by friends: the Koran, Hadith, and Ijtihad. The ijtihad techniques of the companions varied according to their scientific capacity. In addition, the interpretation of the Companions is considered to be the authoritative interpretation after the Qur'an and Hadith, because the Companions really understand the history of the revelation of the verses. The quality of the history of the interpretation of the Companions also needs to be analyzed for its status, but there are also many credible paths of transmission.